Some Further Results on the Reduction of Two-Dimensional Systems - Dongmei Li; Yingying Gui; Jinwang Liu; Man Wu (Complexity)
The reduction of two-dimensional systems plays an important role in the theory of systems, which is closely associated with the equivalence of the bivariate polynomial matrices. In this paper, the equivalence problems on several classes of bivariate polynomial matrices are investigated. Some new results on the equivalence of these matrices are obtained. These results are useful for reducing two-dimensional systems.